Integrative taxonomy identifies new (and old) species in the Lasioglossum (Dialictus) tegulare (Robertson) species group (Hymenoptera, Halictidae) - Gibbs, Jason (Zootaxa, 2009)
An integrative taxonomic approach that utilizes the DNA barcode region of cytochrome c oxidase subunit 1 in conjunction with traditional morphological approaches identifies five distinct species previously recognized as Lasioglossum (Dialictus) tegulare (Robertson). Differences in DNA sequences and congruent, albeit minor, morphological variation support separation of L. tegulare into five species. Unique nucleotide substitution patterns for each species allows for character-based diagnostics using DNA barcodes. The names L. ellisiae (Sandhouse) and L. lepidii (Graenicher) are removed from synonymy. Two new species, L. puteulanum Gibbs sp. n. and L. carlinvillense Gibbs sp. n., are described. A key is provided, which permits the identification of both males and females. The utility of the DNA barcode region as part of an integrative taxonomic framework is discussed.